Charge Transport and Magnetoresistive Mechanisms in Samarium-Doped Manganite Nanoparticles and Their Polypyrrole Nanocomposite - Dutta, Supriya; Rakshit, Soumen; Jana, Paresh Chandra; Sahana, Animesh; Gupta, Kajal (Asian Journal of Chemistry, 2026)
A detailed investigation of charge transport, encompassing direct-current (DC) and alternating-current (AC) conduction, was performed for samarium-doped manganite nanoparticles and their polypyrrole (PPy)-based nanocomposites. The electrical transport characteristics of the pristine manganite and nanocomposite systems were examined as a function of temperature, magnetic field and samarium concentration. The pristine manganite exhibits characteristic polycrystalline magnetoresistance (MR), with MR increasing from 55% for the lowest samarium concentration (M1) to 75% for the highest concentration (M5) at 50 K. Spin-polarized tunneling across grain boundaries constitutes the dominant MR mechanism, with the temperature dependence supporting the role of suppressed spin fluctuations. The nanocomposites exhibit anomalous, fluctuation-like field-dependent MR behaviour that varies with temperature and samarium concentration, with the effect being most pronounced at lower samarium concentrations over the 50-250 K temperature range. This behaviour is attributed to the competition between weak localization and charge-carrier delocalization within a core-shell architecture, mediated by intermediate exchange coupling and the incorporation of polypyrrole. The distinct transport and magnetoresistance responses of the manganite nanoparticles and PPy-based nanocomposites provide insight into the interplay between grain-boundary effects, magnetic exchange interactions and polymer-mediated charge transport.